Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s11934-020-0959-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of Renal Cell Carcinoma and Other Renal Masses in the Kidney Graft

Abstract: Purpose of Review Renal masses in the kidney graft pose an important clinical dilemma, balancing graft function against the need for cancer control. Recent Findings Donor origin cancers in the renal graft can be classified as 'donor transmitted' or 'donor derived'. The landmark TracerX Renal changed our understanding of renal cell carcinoma oncogenesis, demonstrating that key mutations in childhood lead to clinically apparent tumours in later life. Identified pre-operatively, contemporary evidence suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Typically, allograft RCC after transplant is diagnosed 5–15 years following transplantation. Although DNA analysis was not conducted in our case, the early appearance of the malignancy suggests the possibility of it being donor-derived RCC, which is supported by the results of a significant retrospective study that observed that de novo malignancies tend to occur beyond 2 years after transplant, and those found in the earlier stages following transplantation are more likely to be donor-derived [ 7 ].…”
Section: Discussionsupporting
confidence: 57%
“…Typically, allograft RCC after transplant is diagnosed 5–15 years following transplantation. Although DNA analysis was not conducted in our case, the early appearance of the malignancy suggests the possibility of it being donor-derived RCC, which is supported by the results of a significant retrospective study that observed that de novo malignancies tend to occur beyond 2 years after transplant, and those found in the earlier stages following transplantation are more likely to be donor-derived [ 7 ].…”
Section: Discussionsupporting
confidence: 57%
“…RCC is a highly aggressive cancer with unremarkable initial symptoms [ 23 ]. Nearly 30% of RCC patients have developed metastasis at the time of first diagnosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%